Hubungan Perilaku Caring Perawat dengan Kecemasan pada Klien di Ruang Zaal Interna - Ayu, Gadis; Saswati, Nofrida; Dasuki, Dasuki (NHM PRESS, 2024)
Caring behavior towards clients by providing care both verbally and non-verbally and understanding the client's psychological condition, as well as providing appropriate information to help reduce the anxiety experienced by the client. Problems that can arise from hospitals are usually in the form of anxiety, a sense of loss, and fear of actions taken by the hospital, if these problems are not resolved it will affect psychosocial development. This research is a quantitative research using a cross sectional research design. The population in this study amounted to 744 respondents. The sampling technique Accidental Sampling uses a purposive sampling method, totaling 88 respondents. The research was carried out in the internal room at Nurdin Hamzah Hospital, East Tanjung Jabung Regency. And carried out from 26 June – 26 July until July 2023. Data was obtained using a questionnaire. Data analysis was carried out using univariate and bivariate analysis using the chi square test. Based on the results of statistical tests, it shows that there is a relationship between nurses' caring behavior and anxiety in patients in the Zaal Interna Room at Nurdin Hamzah Regional Hospital, East Tanjung Jabung Regency, with the statistical test results obtaining a p-value = 0.000 (<0.05). The results of the research show a relationship between nurses' caring behavior and anxiety in patients in the internal ward. Recommendations for hospitals to apply caring principles in providing nursing care to clients.